2017
DOI: 10.1021/acs.orglett.7b03325
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed C–H Activation of Salicylaldehyde and Decarboxylative Coupling of Alkynoic Acids for the Selective Synthesis of Homoisoflavonoids and Flavones

Abstract: Homoisoflavonoids were formed in DMSO exclusively, and flavones were formed in t-AmOH when salicylaldehyde and alkynoic acids reacted with [Ru(p-cymene)Cl] and CsOAc. They were formed through C-H activation of salicylaldehyde and decarboxylative coupling of alkynoic acid. This reaction system showed good yields, broad substrate scope, and good functional group tolerance. It was found that chalcone was an intermediate in the formation of both homoisoflavonoid and flavone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…In 2017, Lee’s research group exploited [Ru( p -cymene) 2 Cl 2 ] 2 to promote the C–H activation of salicylaldehyde 94 and trigger decarboxylative coupling with alkynoic acids 95 to reach obtain flavonoids 96, 97 ( Scheme 40 ) [ 101 ].…”
Section: Quercetin and Luteolinmentioning
confidence: 99%
“…In 2017, Lee’s research group exploited [Ru( p -cymene) 2 Cl 2 ] 2 to promote the C–H activation of salicylaldehyde 94 and trigger decarboxylative coupling with alkynoic acids 95 to reach obtain flavonoids 96, 97 ( Scheme 40 ) [ 101 ].…”
Section: Quercetin and Luteolinmentioning
confidence: 99%
“…In 2017, our group reported that a Ru-catalyzed decarboxylative coupling of arylpropynoic acids and salicylaldehyde formed homoisoflavonoids (in DMSO solvent) and flavones (in tert-amyl alcohol solvent) (Scheme 31). 36 It was observed that 2 equivalents of salicylaldehyde reacted with the alkynoic acid to give homoisoflavonoids. Chalcone is an intermediate in the formation of both products.…”
Section: Scheme 30 Coupling With Hypervalent Iodine Reagentsmentioning
confidence: 99%
“…In a serendipitous discovery, Lee and co-workers developed an interesting ruthenium-catalyzed synthesis of 2-arylhomo-isoflavonoid 179 scaffolds by reacting salicylaldehyde and alkynoic acids via C-H activation, as depicted in Scheme 6. 99 The reaction is proposed to proceed via initial formation of chalcone 175 that undergoes intramolecular cyclization to provide the flavonoid intermediate 176 .…”
Section: Biological Activities Of Hifsmentioning
confidence: 99%